PENERAPAN EKONOMI DIGITAL DALAM PENCATATAN LAPORAN KEUANGAN - Hendy Satria; Putri Dwi; Irani Dewi; Roynaldy Setiady D.S; Raja Della Putri Shinta; Tri Julita Putri; Mustari Ramadoni (LPPM ITB AAS Indonesia Surakarta, 2023)
This study aims to determine the activities of the 2022 P2EM KKN STIE Pembangunan Tanjungpinang in an effort to share knowledge both from the system. management and accounting to the public so that it can be accepted and used to improve the quality of life. Community Service Activities (PPM) at STIE Pembangunan Tanjungpinang refer to the Strategic Plan (Renstra) as outlined in the Research Master Plan (RIP) of the STIE Pembangunan Tanjungpinang Service Strategic Plan which synergizes research and community service so that it is sustainable, related and relevant in terms of time and problems. . Micro, Small and Medium Enterprises or what can be called UMKM, is a form of community small business whose founders are based on someone's initiative. MSMEs are business actors engaged in various business fields, which prioritize the interests of the community. The 2022 P2EM Community Service Program at STIE Pembangunan Tanjungpinang also provides recommendations for MSMEs to be able to understand how to use the BukuKas application, then provide assistance to MSMEs in recording initial data such as recording the cost of goods sold in daily transactions for receipts and expenses. This research was carried out by conducting community service activities using the